The Effect of Saffron Administration on Spatial Memory with a Neuroinflammatory Approach in Rattus norvegicus IUGR Model Pups - Angeline Novia Toemon; Galih Indra Permana; Ira Jayanti (An Idea Health Journal, 2026)
Intrauterine growth restriction (IUGR) is a condition of fetal growth disorders associated with an increased risk of neurological disorders due to neuroinflammatory activation. Saffron (Crocus sativus L.) is known to have anti-inflammatory and neuroprotective effects, but its mechanisms in IUGR conditions are still not fully understood. This study aims to analyze the effect of saffron extract administration on spatial memory and neuroinflammatory responses in IUGR rat pups. This study was a true experimental study with a post-test only control group design. Wistar rats were divided into three groups: normal (K1), IUGR with 50% dietary restriction (K2), and IUGR with saffron administration of 15.68 mg/kgBW/day (K3). Spatial memory was measured using the Y-maze test (spontaneous alternation). Neuroinflammatory parameters included TNF-α and IL-1β levels (ELISA) and NF-κB expression (immunohistochemistry). Data analysis used the Kruskal-Wallis and Spearman tests (r< 0.05). The results showed that there was no significant difference in spatial memory between groups (r> 0.05), although there was a trend towards an increase in the saffron group. However, TNF-α and IL-1β levels and NF-κB expression increased in the IUGR group and decreased significantly after saffron administration. It was concluded that saffron has a neuroprotective effect through modulating neuroinflammation by reducing proinflammatory cytokines and NF-κB activation, although it did not provide significant improvements in spatial memory.